MODEL OF COOPERATIVE LEARNING BY CIRC TYPE TO INCREASE ABILITY READING SHORT STORY: Classroom Action Research to Class VII-A Students of MTsN Sindangsari Kuningan in 2012/2013 - Rosmiati, Tati (2013)
This journal is titled "Model Of Cooperative Learning by CIRC Type to Increase Ability Reading Short Story (Classroom Action Research to Class VII-A Students of MTsN Sindangsari Kuningan in 2012/2013). Background of this research overshadow lowly of ability reading short story to class VII-A MTsN Sindangsari Kuningan an subject Sunda language. The purpose of this study is to increase ability of students and result learning of students in reading short story and also create an atmosphere to learn that fun. This research using method "Classroom Action Research (CAR)" by using two study cycle. Technique used in this research are technique of tes ability of students and observation. As for instrument used there are sheet tes, sheet of guidance of observation teacher activity, and sheet of gidance observation students activity. Based of result of this research which have been do, action execution it have overcome the problem contend of this research, that is improve the ability read the short story of students completely by boundary KKM 75. Result of the learn students based on result tes in this pre-research only 6 students or 15% inclusive of complete category and also 34 students or 85% inclusive of category not yet complete. Average of value a students that is 54. At tes cycle 1 there are 24 students or 60% inclusive of complete category, and also 16 students or 40% inclusive of category not yet complete. Average of value a students that is 76,7. While of result learn at tes cycle II is all students or 100% from 40 students is inclusive of complete category. Average of value a students that is 91,3. The other way, models of cooperative teaching by CIRC type can create an atmosphere to learn that fun. This matter is seen from participation and increase students activity every cycle. Based on this research, can conclused that the model of cooperative learning by CIRC type can to increase ability reading short story. Keywords: Model of co-operative, CIRC, short story Skripsi ini berjudul "Modél Pangajaran Kooperatif Tipe CIRC pikeun Ngaronjatkeun Kamampuh Maca Carita Pondok (Panalungtikan Tindakan Kelas ka Siswa Kelas VII-A MTsN Sindangsari Kuningan Taun Ajaran 2012/2013)". Penelitian ini dilatar belakangi dengan rendahnya kemampuan membaca cerita pendek siswa kelas VII-A MTsN Sindangsari Kuningan dalam mata pelajaran bahasa Sunda. Tujuan yang ingin dicapai dalam skripsi ini adalah untuk meningkatkan kemampuan siswa dan hasil belajar siswa dalam membaca cerita pendek serta menciptakan suasana belajar yang menyenangkan. Metode yang digunakan dalam penelitian ini adalah metode Penelitian Tindakan Kelas (PTK) dengan menggunakan dua siklus pembelajaran. Teknik yang digunakan dalam penelitian ini adalah teknik tes kemampuan siswa dan observasi. Adapun instrumen yang digunakan yaitu lembar tes, lembar pedoman observasi aktivitas guru, dan lembar observasi aktivitas siswa. Berdasarkan hasil penelitian yang telah dilakukan, pelaksanaan tindakan yang dilakukan telah mengatasi masalah dalam penelitian yaitu meningkatkan kemampuan membaca cerita pendek siswa secara tuntas dengan melampaui batas KKM 75. Hasil belajar siswa berdasarkan hasil tes dalam pra penelitian hanya 6 orang atau 15% termasuk kategori tuntas serta 34 orang atau 85% termasuk kategori belum tuntas. Rata-rata nilai yang diperoleh siswa yaitu 54. Pada tes siklus I ada 24 orang atau 60% masuk kategori tuntas, serta 16 orang atau 40% termasuk kategori belum tuntas. Rata-rata nilai yang diperoleh siswa yaitu 76,7. Sedangkan hasil belajar siswa pada tes siklus II adalah seluruh siswa atau 100% dari 40 orang siswa masuk dalam kategori tuntas. Rata-rata nilai yang diperoleh siswa yaitu 91,3. Selain itu, model pembelajaran kooperatif tipe CIRC dapat menciptakan suasana belajar yang menyenangkan. Hal ini terlihat dari partisipasi dan aktivitas siswa yang meningkat dalam setiap siklusnya. Berdasarkan hasil penellitian, bisa disimpulkan bahwa penerapan modél pembelajaran kooperatif tipe CIRC dalam pembelajaran membaca cerita pendek dapat meningkatkan kemampuan siswa dalam membaca cerita pendek. Kata kunci: modél kooperatif, CIRC, carita pondok